Cryptosporidium Species Infections Detected from Fecal Samples of Animal and Human Hosts in South Africa: Systematic Review and Meta-Analysis - Mpho Tawana; ThankGod E. Onyiche; Tsepo Ramatla; Sebolelo Jane Nkhebenyane; Dennis J. Grab; Oriel Thekisoe (Microorganisms)
This study presents a systematic review and meta-analysis approach of Cryptosporidium species prevalence studies in animal and human hosts published between 1980 and 2020 in South Africa. Extensive searches were conducted on three electronic databases including PubMed, ScienceDirect and Google Scholar. The findings indicated an overall pooled prevalence estimate (PPE) of Cryptosporidium spp. infections in animals and humans at 21.5% and 18.1%, respectively. The PCR–RFLP appeared to be the most sensitive diagnostic method with a PPE of 77.8% for the detection of Cryptosporidium spp. infections followed by ELISA (66.7%); LAMP (45.4%); PCR (25.3%); qPCR (20.7%); microscopy (10.1%); IFAT (8.4%); and RDT (7.9%). In animal hosts, C. parvum had the highest PPE of 3.7%, followed by C. andersoni (1.5%), C. ubiquitum (1.4%) and C. bovis (1.0%), while in humans, C. parvum also had the highest PPE of 18.3% followed by C. meleagridis at 0.4%. The data generated in this study indicated that Cryptosporidium spp. infections were highly prevalent in both animals and humans in South Africa, especially in the KwaZulu-Natal and North West provinces. However, we further observed that there was a lack of prevalence studies for both animals and humans in some of the provinces. This study highlights the necessity for a “One Health” strategic approach promoting public hygiene, animal husbandry and regular screening for Cryptosporidium spp. infections in both animals and humans.